Utilization of Information and Communication Technologies (ICTs) Among Basic Rural Secondary School Teachers in Katsina Silization of Information and Communication Technologies (ICTs) Among Basic Rural Secondary School Teachers in Katsina State, Nigeria (British Journal of Multidisciplinary and Advanced Studies, 2022)
The study was conducted in Katsina State with the aim of finding out the extent of utilization of information and communication technologies (ICTs) among basic rural secondary school teachers. Multi-stage sampling procedure was used to sample 260 teachers; structured interview schedule was employed to capture their thoughts on socio-economic characteristics, sources of information, awareness, access, ICTs utilization and constraints. Descriptive (frequency counts, percentages, mean and standard deviation) and inferential statistics (Chi square and Pearson Product Moment Correlation PPMC) were instruments of data analysis. Teachers were mostly males (85.8%), NCE/BED (97.7%) holders with mean age of 34years and 9 years of working experience. Television (  = 2.35) and internet (  = 2.31) were major sources of information with 60.85% having high level of ICTs awareness. Mobile phone (  = 2.08) and internet (  = 1.76) were most accessed ICTs with 53.8% having low level of access to ICTs. Mobile phone (  = 1.71), newspaper ( 1.52) and radio (  = 1.50) as ICTs were mostly utilized. Most (52.3%) teachers had low level of ICTs utilization. Benefits derived were mostly motivation of students (  = 2.45) and facilitating knowledge sharing with colleagues (  = 2.42). Levels of benefits derived (60.4%) and constraints were high and low respectively. Information (r = 0.330), awareness (r = 0.357), benefits (r = 0.162), access (r = 0.770) significantly correlated with respondents’ level of ICTs utilization. Level (52.3%) of ICTs utilization was low notwithstanding that mobile phone; internet, newspaper and radio were mostly utilized.